Georgij Efron: Tagebücher. Band I. (1940-41) (Hollitzer, 2022)
Georgij Sergeevič Ėfron (1925-1944) was the son of the poet Marina Tsvetaeva (1892-1941), and grandson of the art historian who was the founder of the Pushkin State Museum of Fine Arts in Moscow. The German translation of his diaries is a scholarly edition, the first part of the diaries ends in August 1941, when Georgij's mother, after being evacuated from Moscow and unable to find work to support herself and her son, commit suicide. Volume 1: http://e-book.fwf.ac.at/o:1775 Volume 2: http://e-book.fwf.ac.at/o:1776